AKUNTABILITAS PERGURUAN TINGGI ISLAM SWASTA - A. Rusdiana (Jurnal Pendidikan Islam, 2013)
This study aims to assess policies and programs WASDALBIN, constraints in WASDALBIN implement the policy, the steps in implementing policies WASDALBIN PTAIS. The method used descriptive analytic. The unit of analysis of this study determined purposively, is in 3 areas Kopertais I Jakarta, Banten West Java II, and IV Surabaya, which is considered to represent the whole territory of Indonesia. Data were collected through interviews, documentation and observation studies. The result of the research shows that communication is less effective WASDALBIN policy. The policy implementers assume that WASDALBIN policy is less clear, consistent and appropriate. The quality and the proportion of inadequate resources. Performance of policy implementing is less than optimal. The structure of the bureaucracy in the implementation WASDALBIN still convoluted, making it less efficient. This weakness is almost evenly in all regions studied WASDALBI, with slight variations. Conclusion This study shows that the policy WASDALBIN on Kopertais not be implemented optimally.